Negative and positive regulation of human leukocyte antigen class I gene transcription in K562 leukemia cells. - Chen, E (1987)
The mechanism of transcriptional activation of human leukocyte antigen class I genes by gamma interferon and 5-azacytidine was studied in K562 human leukemia cells. Nuclear run-on transcription assays with various protein and RNA synthesis inhibitors yield evidence for both stimulation of a positive regulatory factor and inhibition of an mRNA that codes for a labile repressor. A novel mechanism is proposed to explain how 5-azacytidine can activate repressed genes without affecting DNA methylation.